FAKTOR PENENTU MINAT PENGGUNAAN INSTAGRAM UNTUK PEMBELIAN ONLINE MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN THEORY OF PLANNED BEHAVIOR (TPB) - Bayu Indrayana; Kudang Boro Seminar; Bagus Sartono (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The objective of this research is to examine the factors that determine the interest in using Instagram in making online purchases. This study also analyzes the pattern of attitude relationship, subjective norms, behavioral control, and uses on interest in using Instagram for online purchases. In addition, the purpose of the research is to analyze whether there are contributions of usability and convenience toward the attitudes and easiness in using the Instagram toward the usage. Data analysis tool used is the structural equation modeling (SEM) which is based technology acceptance model (TAM) and theory of planned behavior (TPB). The results showed that subjective norms significantly influence the interest in using Instagram for online purchases; however, behavior control factors, usability and attitude are not significantly influential. Attitude is a factor that has the greatest influence among other factors. Instagram users from companies/businesses that intend to make use of Instagram as their digital marketing media need to pay attention to aspects of attitudes, subjective norms, behavioral control and usability.Key words: model of technology acceptance, consumer behavior, Structural Equation Modelling (SEM), social media